Implementation of Al-Islam Kemuhammadiyahan and Arabic Language (ISMUBA) Curriculum and Hizbul Wathon Scouting Movement Program in Character Building of Junior High School Students - Wibowo, Gumilang (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this research is to describe character values in al-Islam Kemuhammadiyahan and Arabic activities as well as the Hizbul Wathon scouting movement program at SMP 4 Muhammadiyah Medan. In qualitative research, the research approach used is phenomenology. Data were collected through observation, interview, and documentation. The results of this study mention (1) Character values in ISMUBA learning implemented at SMP Muhammadiyah 4 Medna are Honest, caring, polite in communication and daily associations, responsible, istiqomah and progress, true learners, and critical in taking ibrah. Furthermore, the character values in Hizbul Wathon scouting activities are piety to God Almighty, love of nature and human compassion, patriot and knight, obedient and like deliberation, willingness to help and steadfast, diligent, skillful and joyful, thrifty, careful and unpretentious, disciplined, brave and loyal, responsible and trusted and pure in thought, word, and deed. (2) The implementation strategy of student character building through ISMUBA learning at SMP Muhammadiyah 4 Medan begins with planning learning, then implementing learning and conducting assessments. In the learning process, exemplary methods, habituation, advice, and educational punishment are used. ISMUBA learning is carried out using image, video, and natural learning media. Activities are carried out by problem-solving. Furthermore, related to the implementation strategy of student character building through Hizbul Wathon scouting is done by providing education to students through interesting, fun, and challenging activities, by the conditions, situations, and activities of students by not eliminating the assertiveness of discipline enforcement in its implementation.